Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK) on Capital Expenditure (Survey in Districts/Cities in Central Sulawesi - Nanang Qosim (ASIAN PUBLISHER, 2022)
One of the expenditures used to obtain fixed assets and other assets that benefit more than one accounting period, and is able to encourage the facilities and infrastructure of a region to support community productivity and increase capital investment, namely through Capital Expenditure. The purpose of this study is to determine how much PAD, DAK, DAU and Capital Expenditure in Districts / Municipalities during the period 2012-2016, as well as to determine the effect of PAD, DAK, DAU on Capital Expenditure both simultaneously and partially. The research method used in this study was regression of panel data using the Common Effect Model with a research time of 2012-2016 using the Eviews 10 application. The total population in this study is 11 City Districts. The results of this study show that PAD, DAK, DAU are equally influential on Belanj Modal. Partially, PAD, DAK, DAU have a positive effect on capital expenditure. For further research development, it is recommended that researchers add variables, research periods, and use other research objects and models in their analysis techniques. For the Regency / City Government in Central Sulawesi, it is expected to be able to better know the sources of regional revenue that can increase the realization of the capital expenditure budget, so that the regional government is able to allocate the capital expenditure budget properly.